Barriers to and enablers of uptake of and adherence to antiretroviral therapy in the context of integrated HIV and tuberculosis treatment among adults in sub-Saharan Africa: a protocol for a systematic literature review. Issue 10 (28th October 2019) - Momo Kadia, Benjamin; Takah, Noah Fongwen; Akem Dimala, Christian; Smith, Adrian
Abstract : Introduction: The scale-up of integrated Human Immunodeficiency Virus (HIV) and tuberculosis (TB) treatment has been an important intervention to curb the burden of HIV and TB co-infection worldwide. Uptake of and adherence to antiretroviral therapy (ART) are key determinants of the quality and therapeutic endpoints of this intervention. This study aims to conduct an up-to-date collection and synthesis of evidence on barriers to and facilitators of uptake of and adherence to ART in HIV/TB integrated treatment programs in sub-Saharan Africa (SSA). Method: A systematic review of peer-reviewed literature on the uptake of and adherence to ART in the context of integrated therapy for HIV and TB in SSA will be performed. We will review qualitative and quantitative studies reporting on the uptake of and adherence to ART during integrated treatment for TB and HIV among adults. These will include studies that involve HIV-infected TB patients initiating ART and studies involving PLWHA already on ART who are newly diagnosed with TB. Qualitative studies, quantitative studies, randomised trials and observational studies will be included. Six databases including Medline and Embase will be searched for relevant studies published from March 2004 to July 2019. Two authors will independently screen the search output and retrieve full texts of eligible studies. Disagreements between the two authors will be resolved by arbitration by a third author. Data will be abstracted from the eligible studies and synthesis will be done through descriptive synthesis for qualitative data and meta-analysis for quantitative data. Ethics and dissemination: This study will be a review of the literature and will not involve primary collection of individuals' data. Amendments to the protocol will be documented in the final review. The final study will be published in a peer-reviewed journal and presented at conferences. The review is expected to contribute to improving strategies to enhance uptake of and adherence to ART in integrated care. PROSPERO registration number: CRD42019131933.